Perceptions of climate change and variability, impacts and adaptation strategies by rice farmers in south east Nigeria - Oselebe, Happiness Ogba; Nnamani, Catherine Veronica; Efisue, Andrew; Onu, Donatus; Eze, Simeon Okpoto; Ogunji, Johnny O. (Our Nature, 2017)
This study was designed to identify level of awareness/knowledge of rice farmers in South-eastern Nigeria about climate-change; identify adverse effects of climate-variability and change on rice production and determine adaptation strategies used by small holder rice farmers within study area. Multistage purposive and stratified sampling technique was used for the sample selection. Information from 360 respondents was got using Rapid Rural Appraisal (RRA), Focus Group Discussions (FGD), and actual survey with questionnaires. Results showed that the rice farmers were aware of weather changes with grave effects on their rice farms. They reported changes in rainfall regime, intense sunshine, high temperature etc. Of special interest among the adaptation strategies by farmers are the use of inorganic fertilizers, improved rice varieties, cultivation of early maturing varieties, and proper preservation of rice seeds. This study recommends urgent measures to improve resilience of smallholder farmers in rural communities to enable them better adapt to climate-change. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.